Uji Kromatografi Lapis Tipis dan Deteksi Senyawa Antibakteri Fraksi N-Heksan Ekstrak Etanol Daun Pandan Wangi terhadap Methicillin-resistant Staphylococcus aureus - Setiyanto, Riyan; Maulani, Yulita; Marshanda, Camelia; Rifai, Ryan Nur (FORIKES, 2025)
Pandanus amaryllifolius Roxb leaves contain chemical compounds in the form of tannins, saponins, alkaloids, flavonoids, in the pandan wangi plant has antibacterial and antifungal activity. The purpose of this study was to detect the antibacterial compounds of the n-hexane fraction of ethanol extract of pandan wangi leaves against Methicillin-resistant Staphylococcus aureus. Detection of the content of compounds contained in pandan wangi leaves was carried out using thin layer chromatography with dragendrof spray reagent, FeCl3, sitroborate and vanillin sulfuric acid. From the results of thin layer chromatography it was found that pandan wangi leaves contain tannins, flavonoids, alkaloids and saponins. The content of compounds contained in pandan leaves was tested again by bioautography to determine which compounds have antibacterial properties to overcome the resistance of Methicillin-resistant Staphylococcus aureus bacteria. From the results of the thin layer chromatography bioautography test, there were 4 Rf clear zones found in petri dishes. After matching the clear zones, it was discovered that the substances were suspected to be tannins, alkaloids, terpenoids, and saponins. It was concluded that pandan wangi leaves contain tannins, flavonoids, alkaloids, and saponins, with the n-hexane fraction having antibacterial activity against methicillin-resistant Staphylococcus aureus.Keywords: pandan wangi leaves; n-hexane fraction; methicillin-resistant Staphylococcus aureus ABSTRAK Daun pandan wangi (Pandanus amaryllifolius Roxb) mengandung senyawa kimia berupa tannin, saponin, alkoloid, flavonoid, pada tumbuhan pandan wangi memiliki aktivitas antibakteri dan antifungi. Tujuan penelitian ini adalah melakukan deteksi senyawa antibakteri fraksi n-heksan ekstrak etanol daun pandan wangi terhadap Methicillin-resistant Staphylococcus aureus. Deteksi kandungan senyawa yang terkandung dalam daun pandan wangi dilakukan dengan menggunakan kromatografi lapis tipis dengan pereaksi semprot dragendrof, FeCl3, sitroborat dan vanilin asam sulfat. Dari hasil kromatografi lapis tipis didapatkan bahwa daun pandan wangi mempunyai kandungan tanin, flavonoid, alkaloid dan saponin. Kandungan senyawa yang terdapat dalam daun pandan ini diuji lagi dengan bioautografi untuk mengetahui senyawa mana yang mempunyai khasiat sebagai antibakteri untuk mengatasi resistensi bakteri Methicillin-resistant Staphylococcus aureus. Dari hasil uji kromatografi lapis tipis bioautografi didapat ada 4 Rf zona bening yang terdapat dalam petri. Zona bening tersebut setelah kita cocokkan ternyata zat tersebut diduga senyawa tanin, alkaloid, terpenoid dan saponin. Disimpulkan bahwa daun pandan wangi mempunyai kandungan tanin, flavonoid, alkaloid, dan saponin, dengan fraksi n-heksan mempunyai aktivitas antibakteri terhadap Methicillin-resistant Staphylococcus aureus.Kata kunci: daun pandan wangi; fraksi n-heksan; Methicillin-resistant Staphylococcus aureus